2007
DOI: 10.1038/sj.bjc.6603996
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and lung cancer risk in a cohort study of women: dosage, duration and latency

Abstract: Aspirin may reduce the risk of cancer at some sites but its effect at the lung is unclear. We prospectively examined associations between aspirin use and risk of lung cancer in 109 348 women in the Nurses' Health study from 1980 to 2004. During this time, 1360 lung cancers were documented in participants 36 -82 years of age. Aspirin use and smoking were assessed every 2 years. Risk of lung cancer was a non-significant 16% lower for regular aspirin users of one or two tablets per week and a significant 55% high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Independent estimates from 18 studies were used in the meta-analysis of OTC NSAIDs and lung cancer (Peto et al, 1988;Schreinemachers and Everson, 1994;Langman et al, 2000;Paganini-Hill et al, 1989;Cook et al, 2005;Thun et al, 1993;Harris et al, 2002;Akhmedkhanov et al, 2002; Cyclooxygenase-2 (COX-2) blockade in the chemoprevention of cancers of the colon, breast, prostate, and lung 59 Moysich et al, 2002;Holick et al, 2003;Muscat et al, 2003;Ratnasinghe et al, 2002;Hayes et al, 2006;Hernandez-Diaz and Garcia Rodriguez, 2007;Feskanich et al, 2007;Kelly et al, 2008;Van Dyke et al, 2008). Relative risks and odds ratios with 95 % confidence intervals from these reports are shown in Figure 4.…”
Section: Lung Cancermentioning
confidence: 99%
“…Independent estimates from 18 studies were used in the meta-analysis of OTC NSAIDs and lung cancer (Peto et al, 1988;Schreinemachers and Everson, 1994;Langman et al, 2000;Paganini-Hill et al, 1989;Cook et al, 2005;Thun et al, 1993;Harris et al, 2002;Akhmedkhanov et al, 2002; Cyclooxygenase-2 (COX-2) blockade in the chemoprevention of cancers of the colon, breast, prostate, and lung 59 Moysich et al, 2002;Holick et al, 2003;Muscat et al, 2003;Ratnasinghe et al, 2002;Hayes et al, 2006;Hernandez-Diaz and Garcia Rodriguez, 2007;Feskanich et al, 2007;Kelly et al, 2008;Van Dyke et al, 2008). Relative risks and odds ratios with 95 % confidence intervals from these reports are shown in Figure 4.…”
Section: Lung Cancermentioning
confidence: 99%
“…However, reported results of aspirin use and lung cancer risk are conflicting, with both protective [13][14][15][16][17][18][19][20][21] and null effects [22][23][24][25][26][27][28][29][30][31][32] being reported. Three clinical trials focusing on chemoprevention with aspirin reported non-significant protective effects [35][36][37], and a recent pooled analysis of individual-level data from 7 clinical trials of daily aspirin reported a protective effect on lung cancer death, with a protective latent period of about 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this study assessed the role of current NSAID use and did not report the association by duration of use. Other prospective observational studies including the Cancer Prevention Study, National Health and Nutrition Examination Study, the Nurses’ Health Study and Health Professional Follow-Up study did not report risk estimates by histologic subtypes (1013). …”
Section: Discussionmentioning
confidence: 99%
“…Published cohort studies include the Vitamin and Lifestyle Study (VITAL), Iowa Women’s Health Study (IWHS), Health Professional Follow-Up Study (HPFS), National Health and Nutrition Examination Survey (NHANES), Cancer Prevention Study II (CPS) and the Nurses’ Health Study (NHS), which have reported hazard ratios ranging from 0.69 to 1.10 (813). The inconsistent results may be due to heterogeneity in exposure definition such as dosage, frequency, duration of use and adjusted covariates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation